Citocompatibilidade, propriedades antibiofilme e físicas e cimentos endodônticos associados à amoxilina - Andolfatto, Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Sealers associatedwith amoxicillinhave been developed as an alternative to root canal filling. The objectives of this study were to evaluate the cytocompatibility of AH Plus and Sealapex associated with amoxicillin in concentration of 10% of the total weight of sealer (Chapter 1) and evaluate the flow and the setting time of AH Plus sealer and Sealapex associated with amoxicillin at different concentrations and the activity of sealers antibiofilm associated with higher concentrations of amoxicillin which does not alter the physical properties of both sealers (Chapter 2). In Chapter 1 cytocompatibility of the materials was assessed using the L929 fibroblasts exposed for 24 hours with different dilutions of the extracts of pure sealer and associated with amoxicillin. The testing of 3- (4,5-dimethyl-2-thiazolyl) -2,5-diphenyl-2H-tetrazolium (MTT), and neutral red were used for evaluation of cell viability and fluorescence actin and α-tubulin were used for analysis of the cytoskeleton. Data were analyzed using analysis of variance and two criteria Bonferroni post test at 5% significance level. The results showed that incorporation of amoxicillin at a concentration of 10% by weight of the sealer did not decrease the viability of fibroblasts and did not cause structural changes in the cytoskeletal components studied. It is concluded that amoxicillin could be a promising antimicrobial agent to be incorporated in sealers. In chapter 2 the flow and setting time of the sealer pure or associated with amoxicillin from 0.25 to 10% concentrations were evaluated according to no 6876 specification of the International Organization for Standardization (ISO 2012). The antibiofilm evaluation of pure sealer and 1% associated with amoxicillin was performed by direct contact test with Enterococcus faecalis biofilm previously induced in bovine dentin for 14 days. Fresh sealer were in contact with the biofilm... (Complete abstract electronic access below)

Cimentos endodônticos associados à amoxicilina têm sido pesquisados como uma alternativa para obturação do canal radicular. Os objetivos do presente estudo foram: Avaliar a citocompatibilidade do AH Plus e do Sealapex associados com amoxicilina em quantidade de 10% do peso total dos cimentos (Capítulo 1) e avaliar o escoamento e o tempo de presa dos cimentos AH Plus e Sealapex associados à amoxicilina em diferentes concentrações e a atividade antibiofilme dos cimentos associados a uma maior concentração de amoxicilina que não altera as propriedades físicas de ambos os cimentos (Capítulo 2). No Capítulo 1 a citocompatibilidade dos materiais foi avaliada utilizando fibroblastos L929 expostos por 24 horas a diferentes diluições dos extratos dos cimentos puros e associados à amoxicilina. Os ensaios de brometo de 3-(4,5-dimetil-2-tiazolil )-2,5-difenil-2Htetrazólio (MTT) e vermelho neutro foram utilizados para avaliação da viabilidade celular e a fluorescência para actina e α-tubulina foram utilizadas para análise do citoesqueleto. Os dados foram analisados empregando a análise de variância a dois critérios e pós teste de Bonferroni, com nível de significância de 5%. Os resultados mostraram que a incorporação de amoxicilina na concentração de 10% do peso total dos cimentos não diminuiu a viabilidade dos fibroblastos e não causou alterações estruturais nos componentes do citoesqueleto estudados. Conclui-se que à amoxicilina poderia ser um agente antimicrobiano promissor para ser incorporada aos cimentos endodônticos. No Capítulo 2 o escoamento a o tempo de presa dos cimentos puros ou associados à amoxicilina em concentrações de 0,25 a 10% foram estudadas de acordo com a especificação no6876 da Organização Internacional de Padronização (ISO 2012). A avaliação antibiofilme dos cimentos puros e associados à amoxicilina 1% foi realizada por teste de contato...(Resumo completo clicar acesso eletrônico)
Keywords: Amoxicilina; Enterococcus faecalis; Endodontia; Citotoxicidade; Bactérias; Amoxicillin